2010
DOI: 10.1007/s12665-010-0821-y
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater nitrate vulnerability assessment in alluvial aquifer using process-based models and weights-of-evidence method: Lower Savinja Valley case study (Slovenia)

Abstract: This paper describes the implementation of process-based models reflecting relative groundwater nitrate vulnerability of the shallow alluvial Lower Savinja Valley (LSV) aquifer in Slovenia. A spatially explicit identification of the potentially vulnerable priority areas within groundwater bodies at risk from a chemical point of view is being required for cost-effective measures and monitoring planning. The shallow LSV unconfined aquifer system consists of highpermeable Holocene and middle-to low-permeable Plei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…In this framework, the Slovenian Environmental Agency prepares annual reports on the groundwater quantity status which include the groundwater recharge rates for all 21 Slovenian groundwater bodies quantified with the distributed GROWA model (Andjelov et al 2006;Uhan et al 2010;Uhan 2012). On the regional level, GROWA model results are used for the sustainable development of transboundary groundwater bodies, e.g.…”
Section: Use Of Growa Model Results For Water Management-related Issumentioning
confidence: 99%
“…In this framework, the Slovenian Environmental Agency prepares annual reports on the groundwater quantity status which include the groundwater recharge rates for all 21 Slovenian groundwater bodies quantified with the distributed GROWA model (Andjelov et al 2006;Uhan et al 2010;Uhan 2012). On the regional level, GROWA model results are used for the sustainable development of transboundary groundwater bodies, e.g.…”
Section: Use Of Growa Model Results For Water Management-related Issumentioning
confidence: 99%
“…Among the various statistical methods, the Weights of Evidence (WofE, Bonham-Carter 1994) modelling technique has been chosen for its reliability in performing meaningful and scientific defensible groundwater vulnerability maps, which has been proved by various Authors (e.g., Arthur et Uhan et al 2011). WofE is a cell-based modeling technique, which combines different spatial datasets in a Geographical Information System (GIS) environment to analyze and describe their interactions and generate predictive patterns (Bonham-Carter 1994;Raines et al 2000).…”
Section: Weights Of Evidence Technique and Its Application In Hydrogementioning
confidence: 99%
“…Moreover, they allow identifying the likely important sources of contamination (Sorichetta et al 2013) and assessing the relative probability of contamination occurrence (i.e., groundwater vulnerability), considering the simultaneous presence, or absence, of these factors (e.g., Nolan 2001). In this regard, various authors (Worrall and Besien 2005;Twarakavi and Kaluarachchi 2006;Uhan et al 2011) showed how the high flexibility of statistical methods allows more reliable groundwater vulnerability assessments over large areas compared to the ones obtained with other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its user-friendly interface, open source code and extensive regional adaptation, the SWAT model is becoming increasingly popular worldwide Yang et al 2010;Ouyang et al 2010;Kingston and Taylor 2010;Smith and Dragovich 2008;Schuol et al 2008;Salvetti et al 2008;Arnold et al 2000;Tobin and Bennett 2009). Additional uses of the calibrated and validated SWAT model include analysis of the effects of climate and land use changes on catchmentwide hydrologic processes (Saha et al 2014) as well as turbidity control and groundwater nitrate vulnerability assessment (Noh et al 2014;Uhan et al 2011).…”
Section: Introductionmentioning
confidence: 99%